If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -6x = 3y Solving 6 + -6x = 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -6x = -6 + 3y Combine like terms: 6 + -6 = 0 0 + -6x = -6 + 3y -6x = -6 + 3y Divide each side by '-6'. x = 1 + -0.5y Simplifying x = 1 + -0.5y
| 11c+1=67 | | A(9+a)=4(2a+5) | | 54v^2+18v-120=0 | | r=f(w+a) | | Y(2)-3y+2=0 | | 13/10 | | 4.37=19p | | -2x=1/9 | | 8x-5y=66 | | 9(x+2)=9x+18 | | 16=n/3 | | 4=m-0.002 | | -8x+73=y | | -8x+y=73 | | s=4(3.14)zx+6(3.14)z^2 | | (7x^2+6x)-1=0 | | 6-4x=4-3x | | 2a/3×5/6a | | (4,3)m=7 | | 18+r=6 | | 5+91x=39x+9 | | 79+x*x=180 | | 5x+10=-46-3x | | f(x)=3x^2+6x-9 | | 8x-9=7x+2 | | cos(2x)-sin(2x)=2 | | 3m+8=3(4+m)4 | | 1+5x=-7+x | | (6x-2)/3)-12 | | 10-2(x+3)=16 | | 3(x+1)+(2-x)=10 | | 5(x+2)=3(29-2x) |